Neuroinflammation-Induced Upregulation of Glial Cathepsin X Expression and Activity in vivo - Pišlar, Anja; Tratnjek, Larisa; Glavan, Gordana; Zidar, Nace; Živin, Marko; Kos, Janko (Frontiers in Molecular Neuroscience, 2020)
Neuroinflammation is an important factor in the pathogenesis of neurodegenerative diseases. Microglia-derived lysosomal cathepsins have been increasingly recognized as important inflammatory mediators that trigger signaling pathways that aggravate neuroinflammation. In vitro, a contribution to neuroinflammation processes has been shown for cathepsin X: however, the expression patterns and functional role of cathepsin X in neuroinflammatory brain pathology remain elusive. In this study we analyzed the expression, activity, regional distribution and cellular localization of cathepsin X in the rat brain with neuroinflammation-induced neurodegeneration. The unilateral injection of lipopolysaccharide (LPS) induced a strong upregulation of cathepsin X expression and its activity in the ipsilateral striatum. In addition to the striatum, cathepsin X overexpression was detected in other brain areas such as the cerebral cortex, corpus callosum, subventricular zone and external globus pallidus, whereas the upregulation was mainly restricted to activated microglia and reactive astrocytes. Continuous administration of the cathepsin X inhibitor AMS36 indicated protective effects against LPS-induced striatal degeneration, as seen by the attenuated LPS-mediated dilation of the lateral ventricles and partial decreased extent of striatal lesion. Taken together, our results indicate that cathepsin X plays a role as a pathogenic factor in neuroinflammation-induced neurodegeneration and represents a potential therapeutic target for neurodegenerative diseases associated with neuroinflammation.